Kako biramo partnera? - Tadinac Babić, Meri (2003)
In recent years there has been a surge of interest among evolutionary biologists and psychologists in the topic of human mate choice. Trivers's theory of sexual selection and parental investment heavily influenced the research in this field, primarily by launching the strong theoretical and empirical focus on sex differences in human mating strategies. Mating strategies are integrated sets of adaptations that organize and guide an individual's reproductive effort. They influence how individuals select mates, how much mating effort they expend, etc. Those strategies are not necessarily formulated consciously or even accessible to awareness. Due to different selective pressures and adaptive problems posed to men and women, their strategies tended to evolve differently. Many studies found differences between the sexes in the relative importance they place on specific traits in long-term partners. It has been repeatedly shown that women exhibit a stronger preference than men for attributes of ambition, social status and financial wealth in partner, as well as for a desire for children and commitment to family, which are indicative of the partner's ability to acquire and invest the resources necessary for the survival of offspring. Men exhibit a stronger preference than women for indicators of youthfulness, health and physical attractiveness, which are indicative of high reproductive potential, as well as for indicators of sexual fidelity, which are important because of the high costs for men who are cuckolded. However, mating preferences are not the only factor influencing the mating behaviour. Several other forces likely to be important are preferences expressed by members of the opposite sex, ratio of eligible males to females and mate value of the individual who chooses a partner. Some authors have recently proposed that the stability of the partnership may also influence its reproductive output and that a strategy which is more likely to lead to stable partnerships would be to assess one's own relative quality as a mate, form a mate preference based on this self-perception, and choose a partner of similar mate quality. To explore these issues, we have constructed an instrument that is currently presented on the internet, to collect relevant information on factors in choosing a mate on a broad Croatian sample. The instrument consists of three parts. The first part requests biographical data, including age, sex, income, marital status, self-rating of physical attractiveness, sexual orientation and preference for a long-term vs. short-term relationship. The second section requests subject to rate 18 characteristics on a four-point scale on how important or desirable each of them would be in choosing a mate. In the third section subjects are asked to rank 13 characteristics on its desirability in a mate. These data will enable us to test the hypotheses concerning the processes underlying mate choice.